A systematic review of human behaviour in and around floodwater. (August 2020) - Hamilton, Kyra; Demant, Daniel; Peden, Amy E.; Hagger, Martin S.
Abstract: Flooding can have a major impact on people's safety and livelihood. Understanding people's flood-related behaviours may assist in the development of more effective strategies aimed at lessening the impact of floods including mortality and morbidity. This systematic review examined peer-reviewed literature published from January-1989 to April-2019 on human behaviour in and around floodwater to identify behaviour patterns as well as protective and risk factors. We extracted three main themes from a thematic analysis of included studies (N = 54): activities and risk-taking behaviours (n = 24); loss reduction, knowledge, and warnings (n = 37); and diet and hygiene (n = 4). This review had limitations which prevented definitive conclusions being made. What does seem apparent is the limited knowledge of the social psychological mechanisms that guide behavioural responses in a flood event. Further exploration of methods to improve preparedness, increase the likelihood of evacuation, and reduce 'risky' behaviour during floods is needed. Future studies should prioritise addressing these gaps to enhance the evidence-base for reducing the impact of floods including flood-related mortality and morbidity.